Does offshoring shape labor market imperfections? A comparative analysis of Belgian and Dutch firms - Sabien Dobbelaere; Catherine Fuss; Mark Vancauteren (National Bank of Belgium, 2022)
This paper examines the relationship between offshoring and the prevalence and intensity of labor market imperfections at the firm level. For this purpose, we use Belgian and Dutch manufacturing firm-level data over the period 2009-2017 from Business registers and VAT declarations combined with information in the Transaction Trade database that reports values and volumes of international transactions at the country, firm and product level. In both countries, we find that wage markup-pricing stemming from workers' monopoly power is more prevalent than wage markdown-pricing originating from employers' monopsony power. Offshoring benefits Belgian and Dutch employers in that imports of final as well as intermediate goods are associated with a larger prevalence and intensity of wage markdowns. The opposite holds for the prevalence of wage markups. In Belgium, we also find that offshoring is negatively related to the intensity of wage markups measured by workers' bargaining power. The origin of imports matters for the prevalence of labor market imperfections in Belgian firms. This is far less so in Dutch firms, which could be explained by their more global focus and the more global scale of the vertical chain in which they operate.
Keywords: F14; F16; J42; J50; 330; Wage markdowns; wage markups; firm-level offshoring